Prediction of Marital Dissatisfaction Based on the Resilience, Marital Commitment and Rumination - Kazemi, Maryam; Zanganeh Motlagh, Firoozeh (International Journal of Applied Behavioral Sciences, 2020)
Introduction: Resilience and marital commitment can be considered as a protective factor for maintaining the relationship. On other hand, rumination is a psychological vulnerability factor that has negative effects on resilience and marital commitment. The present study was conducted aimed to predict marital dissatisfaction based on resilience, marital commitment, and rumination in couples seeking for separation. Method: The present study was a cross-sectional study in the form of correlational design. 170 women were selected using purposive sampling from all married women referred to the Dispute Resolution Council in Tehran. Data were collected using demographic checklist, structured clinical interviews, Couple Burnout Measurement, Resilience Scale, rumination questionnaire, and marital commitment scale. Data were analyzed by Pearson correlation coefficient and multiple regression. Results: the results showed that triple components of commitment had a significant and indirect relationship with couple burnout (p< 0.05). Also, there was a significant indirect relationship between rumination with couple burnout and resilience with couple burnout (p< 0.05). Considering the Beta weight based on the first model showed that a standard deviation of change in rumination constituted 0.43 standard deviation of couple burnout. Also, beta coefficients in the second model indicated that a standard deviation of the simultaneous change in rumination dimensions and moral commitment would explain 0.43 and 0.312 standard deviations in couple burnout, respectively (all p's<0.01). Conclusion: These results indicate the role of psychological components in predicting the marital satisfaction and can have clinical applications in designing clinical interventions.